METHODOLOGICAL FOUNDATIONS OF TEACHING THE RUSSIAN LANGUAGE IN MODERN EDUCATION - Ulashova Nilufar Dadaboyevna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article examines modern strategies and instructional techniques used in teaching the Russian language in contemporary educational contexts. Ongoing changes in pedagogical theory and practice have led to a shift from traditional, form-oriented instruction toward approaches that emphasize communicative competence, learner  autonomy,  and  meaningful  language  use.  The  study  analyzes  key methodological  trends,  including  communicative  teaching,  learner-centered instruction, task-based and project-based learning, as well as interactive and reflective practices. Special attention is given to the role of instructional methods in enhancing students’  cognitive  engagement,  motivation,  and  practical  language  skills.  The analysis  shows  that  the  systematic  integration  of  diverse  teaching  strategies  and techniques  creates  favorable  conditions  for  effective  language  acquisition  and supports  the  development  of  functional  communicative  competence.  The  findings highlight  that  successful  Russian  language  teaching  depends  on  the  purposeful combination  of  modern  pedagogical  approaches  adapted  to  learners’  needs  and educational objectives. The results of the study may be useful for language teachers, curriculum designers, and researchers interested in improving the quality of Russian language education.